Physiological and molecular mechanisms mediating xylem Na+ loading in barley in the context of salinity stress tolerance - Zhu, Min; Zhou, Meixue; Shabala, Lana; Shabala, Sergey (Plant, cell and environment, 2017)
Time‐dependent kinetics of xylem Na+ loading was investigated using a large number of barley genotypes contrasting in their salinity tolerance. Salt‐sensitive varieties were less efficient in controlling xylem Na+ loading and showed a gradual increase in the xylem Na+ content over the time. To understand underlying ionic and molecular mechanisms, net fluxes of Ca2+, K+ and Na+ were measured from the xylem parenchyma tissue in response to H2O2 and ABA; both of them associated with salinity stress signalling. Our results indicate that NADPH oxidase‐mediated apoplastic H2O2 production acts upstream of the xylem Na+ loading and is causally related to ROS‐inducible Ca2+ uptake systems in the root stelar tissue. It was also found that ABA regulates (directly or indirectly) the process of Na+ retrieval from the xylem and the significant reduction of Na+ and K+ fluxes induced by bumetanide are indicative of a major role of chloride cation co‐transporter (CCC) on xylem ion loading. Transcript levels of HvHKT1;5_like and HvSOS1_like genes in the root stele were observed to decrease after salt stress, while there was an increase in HvSKOR_like gene, indicating that these ion transporters are involved in primary Na+/K+ movement into/out of xylem.